Dynamic Regulation of Circulating microRNAs During Acute Exercise and Long-Term Exercise Training in Basketball Athletes - Li, Yongqin; Yao, Mengchao; Zhou, Qiulian; Cheng, Yan; Che, Lin; Xu, Jiahong; Xiao, Junjie; Shen, Zhongming; Bei, Yihua (Frontiers in Physiology, 2018)
Emerging evidence indicates the beneficial effects of physical exercise on human health, which depends on the intensity, training time, exercise type, environmental factors and the personal health status. Conventional biomarkers provide limited insight into the exercise-induced adaptive processes. Circulating microRNAs (miRNAs, miRs) are dynamically regulated in response to acute exhaustive exercise and sustained rowing, running and cycling exercises. However, circulating miRNAs response to long-term basketball exercise remains unknown. Here, we enrolled ten basketball athletes who will attend a basketball season for 3 months. Specifically, circulating miRNAs which were involved in angiogenesis, inflammation and enriched in muscle and/or cardiac tissues were analyzed at baseline, immediately following acute exhaustive exercise and after 3-month basketball matches in competitive male basketball athletes. Circulating miR-208b was decreased and miR-221 was increased after 3-month basketball exercise, while circulating miR-221, miR-21, miR-146 and miR-210 were reduced at post-acute exercise. The change of miR-146 (baseline vs. post-acute exercise) showed linear correlations with baseline levels of cardiac marker CKMB and the changes of inflammation marker Hs-CRP (baseline vs. post-acute exercise). Besides, linear correlation was observed between miR-208b changes (baseline vs. after long-term exercise) and AT VO2 (baseline). The changes of miR-221 (baseline vs. after long-term exercise) were significantly correlated with AT VO2, peak work load and CK (after 3-month basketball matches). Although further studies are needed, present findings set the stage for defining circulating miRNAs as biomarkers and suggesting their physiological roles in long-term exercise induced cardiovascular adaptation.